A Modest Programme for the Improvement of law Teaching - Thomas, J C (Victoria University of Wellington Law Review, 1999)
In this article, John Thomas looks at the efforts at Victoria University of Wellington over the past decade to improve law teaching and proposes a more comprehensive approach.